A Comparative Cost Analysis of Cleft Lip Adhesion and Nasoalveolar Molding before Formal Cleft Lip Repair. Issue 6 (December 2015) - Shay, Paul L.; Goldstein, Jesse A.; Paliga, J. Thomas; Wink, Jason; Jackson, Oksana A.; Low, David; Bartlett, Scott P.; Taylor, Jesse A.
Abstract : Background: Patients with complete cleft lip and palate may benefit from cleft lip adhesion or nasoalveolar molding before formal cleft lip repair. The authors compared the relative costs to insurers of these two treatment modalities and the burden of care to families. Methods: A retrospective analysis was performed of cleft lip and palate patients treated with nasoalveolar molding or cleft lip adhesion at The Children's Hospital of Philadelphia between January of 2007 and June of 2012. Demographic, appointment, and surgical data were reviewed; surgical, inpatient hospital, and orthodontic charges and costs were obtained. Multivariate linear regression and two-sample, two-tailed independent t tests were performed to compare cost and appointment data between groups. Results: Forty-two cleft adhesion and 35 nasoalveolar molding patients met inclusion criteria. Mean costs for nasoalveolar molding were 3550.24 ± 667.27. Cleft adhesion costs, consisting of both hospital and surgical costs, were 9370.55 ± 1691.79. Analysis of log costs demonstrated a significant difference between the groups, with the mean total cost for nasoalveolar molding significantly lower than that for adhesion ( p < 0.0001). Nasoalveolar molding patients had significantly more made, cancelled, no-show, and missed visits and a higher missed percentage than adhesion patients ( p < 0.0001) for all except no-show appointments, ( p = 0.0199), indicating a higher burden of care to families. Conclusions: Nasoalveolar molding may cost less before formal cleft lip repair treatment than cleft lip adhesion. Third-party payers who cover adhesion and not nasoalveolar molding may not be acting in their own best interest. Nasoalveolar molding places a higher burden of care on families, and this fact should be considered in planning treatment.